The concentration of maternal sacubitril/valsartan transferred into human milk is negligible - Falconi, Sirin; Okimi, Abiodun; Wesley, Shaun; Sethi, Pooja; Datta, Palika; Krutsch, Kaytlin (Frontiers in Public Health, 2024)
Background: Peripartum cardiomyopathy (PPCM) is a common cause of heart failure (HF) in the peripartum. Some medications are considered safe while breastfeeding. However, sacubitril/valsartan (Entresto), although efficacious, is not recommended in breastfeeding women for fear of adverse infant development and no published data stating otherwise.Objectives: Assess the transfer of sacubitril/valsartan into human milk and evaluate the infant's risk of drug exposure.The InfantRisk Human Milk Biorepository released samples and corresponding health information from 5 breastfeeding maternal-infant dyads exposed to sacubitril/valsartan. Sacubitril, valsartan, and LBQ657 (sacubitril active metabolite) concentrations were determined using liquid chromatography mass spectrometry (LC/MS/MS) from timed samples 0, 1, 2, 4, 6, 8, 10, and 12 hours following medication administration at steady state conditions.Results: Valsartan levels were below the detection limit of 0.19 ng/mL in all milk samples. Sacubitril was measurable in all milk samples of the five participants, peaking one hour after drug administration at a mean concentration of 1.52 ng/mL for a total infant dose of 0.00049 mg/kg/12 hours and relative infant dose (RID) calculated at 0.01%. The maximum concentration of its active metabolite LBQ657 in the milk samples was observed four hours after medication administration and declined over the remaining 12-hour dosing interval, for an average concentration of 9.5 ng/ml. The total infant dose was 0.00071 mg/kg/12 hours and RID was 0.22%. Two mothers reported continuing to breastfeed while taking sacubitril/valsartan; both mothers stated observing no negative effects in their breastfed infants.The transfer of sacubitril/valsartan into human milk is minimal. These concentrations are unlikely to pose a significant risk to breastfeeding infants with a combined calculated relative infant dose of <0.25%, far lower than the industry safety standards (RID <10%).